The (first) Apocalypse of James V,3: 24,10 - 44,10 (TFAOJ) - Schoedel, William R. (BrillOnline Reference Works, 2012)
The third tractate in Codex V is entitled The Apocalypse of James in the subscription (44,9-10) and in a secondary superscription (24,11). To distinguish this tractate from the following one, which bears the same title, we have followed the lead of Böhlig (1) and have added the word "first." The text has been lost at the bottom few lines of pp. 25-34; and pp. 35-44 show increasingly severe damage to both the top and bottom of each page